Perancangan Teknologi Private Cloud Computing Sebagai Sarana Infrastruktur System Online di Universitas Islam Negeri Makassar - Wahyuddin saputra ririn; Nahrun Hartono (Prodi Sistem Informasi UIN Alauddin, 2021)
The need for information technology infrastructure is increasing along with the increasing need for IT resources. One of these needs is the construction and development of a data center. To meet this need, an increase in computing capacity is needed, by procuring new servers. However, there are consequences of this decision, the organization will face several new problems in increasing management, namely the costs spent for these purposes are quite large. Cloud Computing is a technology that can help solve the problem of limited bandwidth and storage space. By using Proxmox VE as a tool to manage server virtualization. This is what makes the author interested in proposing the Design of Private Cloud Computing Technology as an Online System Infrastructure Facility at the Makassar State Islamic University. The purpose of this research is to maximize the performance of the infrastructure that has been used so that it can reduce the cost of using licensed software. The type of research used is experimental research, using data collection methods, namely interviews, observations and literature studies. This design is tested using a black box. The results of this study resulted in the design of an As Service (IaaS) Cloud infrastructure that runs on a local network. The conclusion of this study is that by utilizing Proxmox VE in building a Cloud service (IaaS) it can maximize the performance of a server and can reduce the use of licensed software